Characterization of trajectories and drag coefficients of large wood in sharp river bends from flume experiments. Issue 4 (9th December 2022) - Innocenti, Lorenzo; Branß, Till; Zaid, Bahaeldeen; Aberle, Jochen; Solari, Luca
Abstract: The transport of large wood (LW) has been a focus of research in the last decades because of its importance for river ecosystems, fluvial dynamics and flood protection. Riverine processes connected with the presence of LW have largely been based on laboratory experiments carried out in straight or weakly bended channels. The dynamics of LW in sharp river bends has received less attention, so there exist many open questions regarding how LW is transported through such channel parts. For this reason, this paper presents results of unique laboratory experiments designed to study the trajectories of single wooden dowels in sharp bends. Dowel trajectories were determined for four dowel sizes, two initial dowel orientations with respect to the main channel axis and three inlet positions. Information about the 3D velocity field in the bend were obtained from a previous study that used the same channel with identical hydraulic boundary conditions. Furthermore, a force‐balance analysis was developed for interpreting the dowel trajectory and drag coefficient of LW in sharp river bends. The experimental results show that the dowel length is the main parameter controlling dowel trajectory in a sharp bend, and indicate the role of inertial effects that drive the dowel drift along the bend. The obtained drag coefficients ranged between 0.35 and 1, which is in agreement with previous values for submerged, or semi‐submerged, fixed pieces of wood in straight river reaches. Abstract : We report experience of rather unique laboratory experiments for investigating the dynamics of transported large wood (LW) in sharp river bends. The key role played by the wood piece dimensions is highlighted as well as the importance of inertial effects in defining the trajectory of the LW. Moreover, values of the drag area and drag coefficient are provided for floating LW elements transported in a sharp bend—that is, in the presence of secondary flows.